2020
DOI: 10.1108/dat-02-2020-0010
|View full text |Cite
|
Sign up to set email alerts
|

Daily use of alcohol in the Norwegian general population: Prevalence and associated factors

Abstract: Purpose Harmful use of alcohol is a major public health problem. While harm is often researched in the context of heavy drinking episodes, high-frequency drinking, even when drinking moderate quantities, constitutes a health risk in a longer perspective. The purpose of this paper is to examine the prevalence of daily use of alcohol in the Norwegian general population and to assess sociodemographic, mental health-related and personal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
2
1
1
Order By: Relevance
“…Adjusted for all variables, daily use of alcohol retained its association with depression. The detected association between alcohol use and depression is in line with a range of studies ( 23 ), including a recent Norwegian population study in which having anxiety or depression was associated with daily alcohol use ( 24 ). Thus, use of alcohol appears to be relatively independent from external circumstances.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Adjusted for all variables, daily use of alcohol retained its association with depression. The detected association between alcohol use and depression is in line with a range of studies ( 23 ), including a recent Norwegian population study in which having anxiety or depression was associated with daily alcohol use ( 24 ). Thus, use of alcohol appears to be relatively independent from external circumstances.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, one should be cautious when comparing prevalence rates related to the use of alcohol and addictive drugs to previously established prevalence rates in the general population. In comparison to previously established prevalence rates (15,24), it appears that the rate of daily alcohol use is similar, whereas the rates of "sometimes/weekly/daily" use of cannabis, sedatives, and painkillers are lower in this study. However, it has been argued that skewed samples are more prone to affect prevalence rates of substance use, while less prone to affect associations between predictors and substance use outcomes (43,44).…”
Section: Study Limitationscontrasting
confidence: 54%
“…Adjusted for all variables, daily use of alcohol retained its association with depression. The detected association between alcohol use and depression is in line with a range of studies [18], including a recent Norwegian population study in which having anxiety or depression was associated with daily alcohol use [19]. Thus, use of alcohol appears to be relatively independent from external circumstances.…”
Section: Discussionsupporting
confidence: 84%
“…However, while weekly drinking was associated with less health problems, daily drinking may be associated with more health problems. A recent study showed that those with the most frequent drinking pattern (daily alcohol intake) had higher risk of experiencing psychological distress, compared to those with a less frequent drinking pattern (Bonsaksen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%